Mechanisms of Tolerance Induction by Hematopoietic Chimerism: The Immune Perspective. (3rd January 2017) - Yolcu, Esma S.; Shirwan, Haval; Askenasy, Nadir
Summary: Hematopoietic chimerism is one of the effective approaches to induce tolerance to donor-derived tissue and organ grafts without administration of life-long immunosuppressive therapy. Although experimental efforts to develop such regimens have been ongoing for decades, substantial cumulative toxicity of combined hematopoietic and tissue transplants precludes wide clinical implementation. Tolerance is an active immunological process that includes both peripheral and central mechanisms of mutual education of coresident donor and host immune systems. The major stages include sequential suppression of early alloreactivity, establishment of hematopoietic chimerism and suppressor cells that sustain the state of tolerance, with significant mechanistic and temporal overlap along the tolerization process. Efforts to devise less toxic transplant strategies by reduction of preparatory conditioning focus on modulation rather than deletion of residual host immunity and early reinstitution of regulatory subsets at the central and peripheral levels.